Implementation of occupational safety and health in a medical laboratory: A Qualitative Study - Marisca Jenice Sanaky; Nuril Sofiantin; Army Dwi Israyanti; Nur Ismi (Jurnal Ilmiah Kesehatan Sandi Husada, 2025)
Introduction: Occupational Safety and Health (OSH) plays a vital role in ensuring safe and effective learning environments in medical laboratory education. Academic laboratories pose inherent risks from chemical, biological, physical, and ergonomic hazards. Despite established OSH standards, their implementation in educational laboratory settings remains inconsistent, particularly in developing country contexts. Methods: A qualitative study was conducted in the Medical Laboratory Technology Program laboratory at Politeknik Sandi Karsa, Indonesia. Data were collected through moderate participant observation, semi-structured interviews, and document review. A total of 25 participants were purposively selected, including students, laboratory instructors, laboratory personnel, and program administrators. Data were analysed thematically using an OSH management framework encompassing the preparation, planning, organising, and implementation stages. Results: The study found that OSH implementation was not fully optimised across all management stages. Significant challenges included the absence of structured OSH training and socialisation, a lack of comprehensive laboratory standard operating procedures, unclear organizational roles for OSH responsibilities, inadequate laboratory infrastructure, and inconsistent compliance with personal protective equipment requirements. Additionally, routine monitoring and evaluation of OSH practices were not systematically conducted. Conclusion: These findings suggest that limited institutional commitment, insufficient awareness, and infrastructural constraints hinder effective OSH implementation. Strengthening governance mechanisms, enhancing human resource capacity, establishing clear procedures, and improving facilities are critical to advancing laboratory safety. Comprehensive and sustained OSH management is essential to minimize occupational risks and to promote a safe and productive academic medical laboratory environment.